2023
DOI: 10.1002/smll.202206838
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Mismatch–Induced Formation of Copper Nanoplates with Embedded Ultrasmall Platinum or Palladium Cores for Tunable Optical Properties

Abstract: Although noble metal nanocrystals have been studied extensively in the past decades, the shape‐controlled synthesis of non‐noble metal nanocrystals has remained challenging with limited success, which is a grand obstacle to their wide applications. Herein, a novel lattice mismatch–involved shape‐control mechanism of Cu nanocrystals in a seed‐mediated synthesis is reported, which can produce Cu nanoplates in high yield with tailored sizes (28–130 nm), holding great potential in optical and catalytic application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The choice of phase through lattice mismatch indices allows for the preparation of Cu surfaces with planar defects of different outer shapes, as well as the adjustment of surface layer sizes through the content of seeds such as Pd, forming structures like plates that are significantly larger than the core (Figure 1a). [14e] Moreover, in terms of controlling the shell thickness, Feng and colleagues successfully obtained Au@Rh(OH) 3 core‐shell structures with varying shell thicknesses through the thiol ligand‐mediated interfacial energy [10] . In fact, ligands selectively adsorb on specific facets of noble metal nanocrystals, leading to facet‐dependent rates of crystal growth, [23e] which has given rise to the preparation of various 2D materials that affect the surface noble metals as substrates [35] .…”
Section: Driving Forces Of Strain On Noble Metal Surface and Characte...mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of phase through lattice mismatch indices allows for the preparation of Cu surfaces with planar defects of different outer shapes, as well as the adjustment of surface layer sizes through the content of seeds such as Pd, forming structures like plates that are significantly larger than the core (Figure 1a). [14e] Moreover, in terms of controlling the shell thickness, Feng and colleagues successfully obtained Au@Rh(OH) 3 core‐shell structures with varying shell thicknesses through the thiol ligand‐mediated interfacial energy [10] . In fact, ligands selectively adsorb on specific facets of noble metal nanocrystals, leading to facet‐dependent rates of crystal growth, [23e] which has given rise to the preparation of various 2D materials that affect the surface noble metals as substrates [35] .…”
Section: Driving Forces Of Strain On Noble Metal Surface and Characte...mentioning
confidence: 99%
“…In addition to ligand assistance, the driving force of temperature is crucial. Hydrothermal reaction is a commonly used method for stable temperature control, which is capable of achieving metal overlayer coating under different lattice mismatch conditions [14e] . Post hydrothermal structuring control and subsequent reduction reactions, irregular particle cores of β ‐Ni(OH) 2 with unique flower‐like morphology can also complete the doping of Rh in β ‐Ni(OH) 2 through seed‐mediated growth [37] …”
Section: Driving Forces Of Strain On Noble Metal Surface and Characte...mentioning
confidence: 99%
“…The optical properties of Ag and Cu are closely related to their size, morphology, and surface properties [3,[63][64][65][66], which provides the possibility for the regulation of their optical properties by coating a noble metal layer and building core-shell nanostructures. Our group and Yan's group found that the localized surface plasmon resonance (LSPR) of Ag@Au core-shell nanocrystals had a red shift and an increasing intensity compared to Ag nanocrystals (Figure 9a,b) [35,62].…”
Section: Tuning the Optical Propertiesmentioning
confidence: 99%
“…Bimetallic nanocrystals are receiving increasing interest in optics [1][2][3], catalysis [4][5][6][7][8][9][10], and many other fields [11][12][13][14][15]. For example, bimetallic nanocrystals are an excellent class of catalysts for many industrial processes and energy conversion thanks to their intriguing catalytic properties arising from the electronic and geometric interactions between constituent metals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation